Transnasjonale helsepraksiser. Bruk av helsetjenester blant polske arbeidsinnvandrere i Norge - Stachowski, Jakub; Rye, Johan Fredrik (Nordisk tidsskrift for helseforskning, 2017)
Transnational Health Practices Among Polish Labor Migrants in NorwayThe article discusses the use of health-care services among Polish labor migrants in Norway. We apply theories of patient–physician relationship, trust, and transnationalism to analyze a material of qualitative in-depth interviews with eleven Polish labor migrants about their health practices. The material demonstrates how and why many Polish labor migrants evaluate Norwegian primary health care negatively. Their main reason for doing so is the non-paternalistic doctor–patient relationship. They therefore supplement Norwegian health services with health services available in their home country. However, the labor migrants tend to evaluate the Norwegian health system more favorably as time passes. In total, the Poles establish creative, reflexive, competent, and dynamic health practices that go beyond national state borders and combine elements of two health-care systems. We argue that these practices enable migrants to enhance the total quality of their health care.
Keywords: health services; labor migration; transnationalism; Poland; welfare state; helsetjenester; arbeidsinnvandring; transnasjonalisme; Polen; velferdsstat